Double blind randomized comparative study of transdermal fentanyl patch for post operative pain relief in major abdominal surgery as a component of multimodal analgesic therapy - Sangineni, Kalyani Surya Dhanalakshmi; Deolalkar, Anuradha; Parakh, S. C.; Rajuloo, D. Dharma (International Journal of Basic & Clinical Pharmacology, 2016)
Background: There are various methods of alleviating post-operative pain, multimodal analgesia is the recommended practice. Fentanyl patch can also be used in the management of acute postoperative pain. We have done a study to compare the efficacy of fentanyl patch to a placebo patch as a part of multimodal analgesic strategy. Methods: Forty four patients were randomized into two groups. Groups were named as FP (Fentanyl patch) and P (Placebo). The Patch was placed 10-12 hours before surgery and patient was monitored for 72 hours postoperatively for pain by NRS (Numeric Rating Scale). All the patients received regular Paracetamol and Diclofenac Sodium. Tramadol was given as rescue analgesia if the NRS scale was more than 5. Data was analysed using Windows stat version 9.2 from Indostat services. Results: There was statistically significant difference in the consumption of Tramadol in patients with FP group (19.44 mg) as compared to P group (72.22mg) over 72 hours. The Numerical Rating scale was also much lower in the FP group at 8, 16, 24, 32, 40, 48, 56, 64 and 72 hours. Maximum difference in the pain score being at 24 hours for the FP group. No difference in the Sedation, Pruritus, Respiratory depression, Nausea and vomiting scores in the two groups. Conclusions: Transdermal Fentanyl Patch of 25 µg/hr when applied 10-12 hours before surgery provides effective postoperative pain relief after major abdominal surgery as a part of multimodal analgesia.